Strengthening Vocational Education Quality Through the Supervision of Competency Skills Examinations at SMK Bintang Timur Pematangsiantar - Parulian, Hengki; Poltak Pardamean Simarmata; Erwin Sirait; Doris Yolanda Saragih; Sandi Maiko Sihite; Andi Setiadi Manalu; Firinta Togatorop; Jusra Tampubolon (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service activity aims to support the quality assurance of vocational education through the supervision of Competency Skills Examinations (CSE) for vocational high school students. The activity was conducted at SMK Bintang Timur Pematangsiantar on March 2, 2026, involving a total of 30 twelfth-grade students. The implementation of the activity was carried out through direct supervision, examination monitoring, verification of examination procedures, observation of students’ performance, and coordination with the examination committee to ensure that the assessment process complied with the established competency standards and examination guidelines. The external supervisors from Politeknik Bisnis Indonesia were Erwin Sirait, S.Kom., M.Kom., and Viktor M. Siregar, S.Kom., M.Kom. The results showed that the Competency Skills Examination was conducted effectively, orderly, and according to the predetermined schedule. Students were able to complete the examination process in accordance with the established procedures, while the supervision process ensured fairness, transparency, and accountability throughout the assessment activities. This activity has a positive impact on strengthening the quality of vocational education assessment, supporting competency-based evaluation, and enhancing stakeholders’ confidence in the implementation of competency examinations as an important measure of students’ readiness to enter the workforce.